# math

posted by .

3x + 2y + 16x^3z + 6y =

ANSWER: 19x + 8y + 3z

• math -

again, incorrect

when you add/subtract terms they must be "like"
the variables and exponents do not change.

3x + 2y + 16x^3z + 6y
= 3x + 8y + 16x^3z

(the only terms that were "like" were the y terms )

• math -

If the problem has no typos, it can reduce to:

16x^3z + 8y + 3x

• math -

the question is i wrote it wrong
3x + 2y + 16x + 3z + 6y =

• math -

I see three kind of terms, x's , y's and z's

• math -

19x + 8y + 3z

• math -

Right.

## Similar Questions

1. ### algebra

Solve the system by addition or substitution. 16x-4y=20 y=4x-4 I ask for help with this and forgot to add the problem. can anyone help me understand how to do this?
2. ### Algebra

There are two solutions to | 16x - 5 | = 3. The greatest solution is ___. Since the expression, 16x - 5, can be either positive or negative, solve for both. 16x - 5 = 3 16x = 8 x = .5 -(16x - 5) = 3 -16x + 5 = 3 -16x = -2 x = 1/8 You …
3. ### Math

Can you factor these for me? 12x^3 + 6x^2 - 3x - 2 2x^2 +x - 6 25 - 4(x^2 - )^2 y^2 - 3y - 10 (3x - 1)^2 -36 x^3 - 3x^2 - 16x + 48 4x^2 + 7x +3 6x^2 - 19x + 15 5x^4 - 45x^2
4. ### math

3x + 2y + 16x^3z + 6y = ANSWER: 19x + 8y + 3z
5. ### math

3X + 2Y + 16X + 3Z + 6Y = 19x + 8y + 3z
6. ### Math

5(-3x - 2) - (x - 3) = -4(4x + 5) + 13 Answer Multiply factors. -15x - 10 - x + 3 = -16x - 20 +13 Group like terms. -16x - 7 = -16x - 7 Add 16x + 7 to both sides and write the equation as follows 0 = 0
7. ### Algebra

Find the product (1 - 3x) (x^2 - 6x - 4)x^2 A. -3x^5 + 19x^4 + 6x^3 - 4x^2 B. -3x^5 - 19x^4 + 6x^3 - 4x^2 C. -3x^5 + 19x^4 - 6x^3 - 4x^2 D.-3x^5 - 19x^4 - 6x^3 - 4x^2
8. ### Math

I sent this in a little while back but the file got corrupted and I have to re do it and I forgot the answer please if it is not done today I fail the year. Simplify the polynomial 16x^2 + 2 + 2x - 15x^2 - 1 + 14x A:31x^2 + 16x + 1*** …
9. ### Math

1. 16x^2 + 2 + 2x - 15x^2 - 1 + 14x a. 31x^2 + 16x + 1 b. x^2 - 12x + 1 c. x^2 + 16x + 1* d. x^2 + 16x + 2 2. 3x^2 + 6 - 2x + 5x - 4^2 + 9 a. -x^2 + 3x + 15* b. 7x^2 + 3x + 3 c. x^2 - 3x + 15 d. -x^2 + 7x + 15 3. 2x^2 + 6x - 7x + 8 …
10. ### Math

I need helppp D: ---------------- Simplify the expression -4-5(x+8) *-5x-44 *-5x+36 *-x-8 *-20x+8 5x+6(x-2)-8(x-3) *19x+36 *19x+12 *3x-36 *3x-12 x+8<-28 *x<-36 *x<-20 *x<20 *x<36

More Similar Questions